The Masters of Vision. From Visionary Science to Visual Suggestions (diségno, 2021)
The studies of Isaac Newton, in the 17th century, laid the foundations of classical physics. In the 19th century, however, some theories questioned Newtonian physics, whose weakness came from the application of concepts of Euclidean geometry to a space that may not be so. In 1817 Gauss, during his studies on the fifth postulate, formulated the hypothesis that for a point outside a line it was possible to draw more than one line parallel to it. Thus, he laid the premises of non-Euclidean geometry.In 1884 Abbott published the novel Flatland, in which he hypothesized a multi-dimensional space. The cultural debate thus opened up to visionary artistic expressions, derived from equally ‘subversive’ scientific concepts. Not to be neglected are also the studies of Poincaré that led to the topological space. These suggestions were anticipated by Möbius, in 1858, with the single-sided surfaces. The demolition of Newtonian dogmas also intertwined with perception studies. This led to the “impossible objects” of Reutersvär and Lionel and Roger Penrose. In the same years, also Escher shared the same passion for perceptual experiments.The paper aims to highlight the relationship between art and science which, between the 19th and 20th centuries, find a common ‘visionary’ inspiration. Often these paths are intertwined, sometimes one anticipates the other, but together they contribute to open pathways that mark the evolution of thought and art.
Keywords: Non-Euclidean geometries; Topology; Impossible objects; Möbius; Penrose; Escher